(untitled) (Third Sector Social Economic Review, 2026)
This study examines the effects of asymmetric shocks in capacity utilization rate, producer price index, credit interest rate, energy-based commodity prices, non-energy commodity prices, and leading metal commodity prices on Türkiye’s industrial production. The results are important because they explain the effects of negative and positive shocks on Türkiye’s industrial production. The study makes three important contributions to the literature: the simultaneous examination of many variables affecting industrial production, the investigation of the impact of commodity price changes on industrial production, and the use of a nonlinear ARDL (NARDL) model. In this study, the effects of the relevant variables on Türkiye’s industrial production for the period 2007q1-2024q4 were investigated in both the short and long term, as well as in an asymmetric structure. According to the NARDL model results, the effect of an increase in the capacity utilization rate (LKKO) on increasing industrial production is higher compared to other variables. This indicates that policies aimed at improving capacity utilization will have a higher and more positive effect compared to other variables. The importance of stability is noteworthy in non-energy commodities (LNE) and credit interest rates (LKFO). According to the results obtained using the Wald Test, LKFO, LKKO, LNE, energy-containing commodities (LE), and precious metal commodities (LPM) have an asymmetric effect on industrial production in Türkiye in the long term. The producer price index, however, does not have an asymmetric effect in the long term. In the short-term asymmetry test, no significant results were obtained for all independent variables. To increase industrial production in Türkiye, it would be appropriate to create a policy basket that considers all variables simultaneously.